2018
DOI: 10.1021/acs.jafc.7b05035
|View full text |Cite
|
Sign up to set email alerts
|

Hordenine: A Novel Quorum Sensing Inhibitor and Antibiofilm Agent against Pseudomonas aeruginosa

Abstract: The quorum sensing (QS) inhibitory activity of hordenine from sprouting barley against foodborne pathogen Pseudomonas aeruginosa was evaluated for the first time here. At concentrations ranging from 0.5 to 1.0 mg mL, hordenine inhibited the levels of acyl-homoserine lactones. The enhanced susceptibility of hordenine with netilmicin on P. aeruginosa PAO1 biofilm formation as well as their efficiency in disrupting preformed biofilms was also evaluated using scanning electron microscopy and confocal laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 38 publications
13
110
1
1
Order By: Relevance
“…Furthermore, hordenine effectively reduced virulence factors and QS-related gene expression of P. aeruginosa PAO1 [41,42]. It is indicated that the anti-QS potential of hordenine act as a competitive inhibitor for signaling molecules and a novel QS-based agent to defend against foodborne pathogens [41]. Nanoparticles (NPs) like AuNPs was also developed to conjugate with hordenine and hordenine-AuNPs exhibited enhanced anti-biofilm properties on P. aeruginosa PAO1 [43], suggesting nanoparticles-delivered natural compounds could be effectively use in biofilm-based microbial infection.…”
Section: Hordeninementioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, hordenine effectively reduced virulence factors and QS-related gene expression of P. aeruginosa PAO1 [41,42]. It is indicated that the anti-QS potential of hordenine act as a competitive inhibitor for signaling molecules and a novel QS-based agent to defend against foodborne pathogens [41]. Nanoparticles (NPs) like AuNPs was also developed to conjugate with hordenine and hordenine-AuNPs exhibited enhanced anti-biofilm properties on P. aeruginosa PAO1 [43], suggesting nanoparticles-delivered natural compounds could be effectively use in biofilm-based microbial infection.…”
Section: Hordeninementioning
confidence: 96%
“…Furthermore, hordenine effectively reduced virulence factors and QS-related gene expression of P. aeruginosa PAO1 [41,42]. It is indicated that the anti-QS potential of hordenine act as a competitive inhibitor for signaling molecules and a novel QS-based agent to defend against foodborne pathogens [41].…”
Section: Hordeninementioning
confidence: 99%
“…In particular, the production of extracellular virulence factors was partially or completely suppressed in P. aeruginosa cultures grown in the presence of 1 or 10 mM (approximately 2.5 mg/mL) 68 without affecting the growth of the planktonic cultures . Hordenine ( 70 ), a dietary phenolic natural product from sprouting barley, has traditionally been used as a vasoconstrictor and an indirect‐acting adrenergic agent and has also been investigated as a novel QS inhibitor against the formation of pyocyanin at a concentration of 0.5 μM . Zhang and Coenye demonstrated that plant‐derived coumarin ( 71 ) inhibits QS in the P. aeruginosa QSIS2 biosensor strain, reduces protease and pyocyanin production in the range of 1‐3 mM, and suppresses biofilm formation in microtiter plates in different P. aeruginosa strains .…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…151 Hordenine (70), a dietary phenolic natural product from sprouting barley, has traditionally been used as a vasoconstrictor and an indirect-acting adrenergic agent and has also been investigated as a novel QS inhibitor against the formation of pyocyanin at a concentration of 0.5 μM. 152 Zhang and Coenye demonstrated that plant-derived coumarin (71) inhibits QS in the P. aeruginosa QSIS2 biosensor strain, reduces protease and pyocyanin production in the range of 1-3 mM, and suppresses biofilm formation in microtiter plates in different P. aeruginosa strains. 153 In addition to natural products, drug repurposing also plays a critical role in the discovery of antivirulence agents.…”
Section: Pyocyanin Inhibitors From a Natural Product Library And Drmentioning
confidence: 99%
“…Antivirulence therapy is an alternative approach to control bacterial infections, targeting the virulence process rather than the viability of pathogens. This leads to less severe infections at a level that can be cleared by the host's immune system (Loo et al, 2016;Silva, Zimmer, Macedo, & Trentin, 2016;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%